Implementing a Central Bank Issued Digital Currency with Economic Implications Considerations - Mohamed, Hazik (Universitas Muhammadiyah Yogyakarta, 2020)
A central bank-issued digital currency (CBDC) could solve the volatility of a privately-issued cryptocurrency as well as keep intact its potential benefits. This research intended to analyze the possibilities for implementing a CBDC in a viable format that is also Shariah-compliant which may have the capacity to tackle issues plaguing the current financial system. We discuss possible scenarios and the resulting impact and consequences of CBDC implementation, through a deep examination of the benefits, opportunities, costs and issues of several conceptual formats. Methodologically, we used qualitative, comparative and analytical assessments on the critical impact on crucial levers like dilution to monetary policy, and the stability of the financial system. Finally, we found that the best format was a non-interest bearing CBDC for the interbank settlement and wholesale payment systems which would have the least disruption to the economy but strongest monetary policy transmission.